2018
DOI: 10.1111/ina.12511
|View full text |Cite
|
Sign up to set email alerts
|

Asthma‐related outcomes associated with indoor air pollutants among schoolchildren from four informal settlements in two municipalities in the Western Cape Province of South Africa

Abstract: The health impact of indoor air pollution in informal settlement households has not been extensively studied in South Africa. This cross‐sectional study investigated the association between asthma and common indoor exposures among schoolchildren from four informal settlements located in two municipalities in the Western Cape Province. A total of 590 children, aged 9‐11 years, were recruited. The International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire was administered to caregivers. Pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 50 publications
1
20
1
Order By: Relevance
“…In primary school children from Viseu, Portugal, Martins et al [22] reported a slightly lower active wheezing prevalence (11.7%) when compared with that of the present study. Also for primary school children (aged 7-9 years old) from two municipalities in Western Cape Province, South Africa, Olaniyan et al [8] reported a slightly lower prevalence of active wheezing (12.9%) than in the present study. In another study in Portugal, Branco et al [12] reported an active wheezing prevalence of 17.1% for children with less than 5 years old attending nursery schools in Porto and Bragança districts, which was very similar to the prevalence calculated in the present study.…”
Section: Study Site and Populationcontrasting
confidence: 71%
See 1 more Smart Citation
“…In primary school children from Viseu, Portugal, Martins et al [22] reported a slightly lower active wheezing prevalence (11.7%) when compared with that of the present study. Also for primary school children (aged 7-9 years old) from two municipalities in Western Cape Province, South Africa, Olaniyan et al [8] reported a slightly lower prevalence of active wheezing (12.9%) than in the present study. In another study in Portugal, Branco et al [12] reported an active wheezing prevalence of 17.1% for children with less than 5 years old attending nursery schools in Porto and Bragança districts, which was very similar to the prevalence calculated in the present study.…”
Section: Study Site and Populationcontrasting
confidence: 71%
“…Existing literature focused on the association between children's exposure to indoor air pollutants and respiratory health is also limited, and mostly focusing on asthma, thus neglecting childhood wheezing although it is more common and easier to diagnose [8]- [13].…”
Section: Introductionmentioning
confidence: 99%
“…The high rates of severe symptoms seen in low-income countries are concerning, and likely reflect multiple challenges within healthcare systems, which are better equipped to manage acute episodes relating to infectious diseases, rather than chronic non-communicable conditions. In keeping with this, recent research from Nigeria and South Africa has reported high rates of under-diagnosed and untreated asthma in schoolchildren 35 36…”
Section: Discussionmentioning
confidence: 75%
“…Indoor or household air pollution is the result of the use of alternate and polluting fuels as a source of household energy for cooking and heating [ 14 ]. These include solid, biomass and fossil fuels [ 15 , 16 ] as well as kerosene (paraffin) [ 17 , 18 ]. Incomplete combustion often combined with inadequate ventilation of these polluting substances results in a large number of chemical compounds such as particulate matter (PM), sulphur dioxide, nitrogen dioxide, carbon monoxide (CO) and volatile organic compounds that are then inhaled [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%